Antifungal activities of extracts produced by liquid fermentations of Chilean Stereum species against Botrytis cinerea (grey mould agent). (November 2016) - Aqueveque, Pedro; Céspedes, Carlos L.; Alarcón, Julio; Schmeda-Hirschmann, Guillermo; Cañumir, Juan A.; Becerra, José; Silva, Mario; Sterner, Olov; Radrigán, Rudy; Aranda, Mario
Abstract: Extracts obtained from liquid mycelial fermentations of Chilean species of the Stereum genus showed antifungal activity against Botrytis cinerea . Thirty-six strains were evaluated in vivo and in vitro assays, 25 belonging to Stereum hirsutum (Sh) and 11 to Stereum rameale (Sr). Two types of extracts were obtained: EtOAc-extract (liquid phase) and MeOH-extract (mycelial phase). Plate diffusion assay showed that EtOAc-extracts were more active than MeOH-extracts. S. hirsutum included 4 strains with the highest antifungal activity (Sh134-11, Sh144-11, Sh152-11, Sh155-11) and S. rameale highlighted with two strains (Sr25-11, Sr27-11). Effects on the mycelial growth of B. cinerea showed that EtOAc-extracts produced by S. hirsutum (Sh134-11, Sh152-11) inhibited from 1000 μg mL −1, reaching 67 and 49%, respectively. At 2000 μg mL −1, these strains inhibited nearly 80% of mycelial growth. EtOAc-extract of Sh134-11 was more effective to control the sporogenesis, inhibiting in 100% the sporulation at 500 μg mL −1 . Assays showed that Sh134-11 and Sh152-11 exhibited a minimal fungicidal concentration (MFC) of 50 and 100 μg mL −1 respectively and minimal inhibitory concentration (MIC) at 20 μg mL −1 . EtOAc-extracts of Sr25-11 and Sr27-11 showed MFC value at 100 μg mL −1 and MIC at 20 and 50 μg mL −1, respectively. Strawberries treated with 1000 μg mL −1 of Sh134-11 and Sr25-11 reached 82 and 72% of decay inhibition, respectively. Treatments with 2000 μg mL −1 showed a decay inhibition of 90% approximately. In vivo tests are in accordance with the results obtained in vitro assays, confirming the efficacy of Sh134-11 and Sr25-11 to control B. cinerea . Differences in antifungal activities observed in the different strains suggested that the ability to produce bioactive compounds is not homogenously distributed among S. hirsutum and S. rameale . Our study would suggest that submerged fermentations of Chilean S. hirsutum strain Sh134-11 produce extracts, which could be used as possible biofungicides and an alternative to synthetic fungicides. Abstract : Liquid cultures of Chilean Stereum species produced active extracts against Botrytis cinerea . A total of 36 strains were studied, 25 belonging to Stereum hirsutum (Sh) and 11 to Stereum rameale (Sr). The most active extracts (EtOAc) were produced by strains Sh134-11 and Sr25-11. Both extracts inhibited considerably mycelial growth and sporogenesis of B. cinerea . EtOAc-Sh134-11 showed MIC and MFC values at 20 and 50 μg mL −1 respectively against B. cinerea.